Case report: Successful management of Parvimonas micra pneumonia mimicking hematogenous Staphylococcus aureus pneumonia - Feng, Yanmei; Wu, Chunxia; Huang, Xiaohui; Huang, Xia; Peng, Li; Guo, Rui (Frontiers in Medicine, 2022)
Parvimonas micra is an anaerobic Gram-positive coccus frequently found in the oral cavity and gastrointestinal tract, but rarely in the lung. Therefore, pneumonia caused by P. micra is also rare. Although there are some reports of P. micra related pneumonia due to aspiration or blood-borne infection with definite remote infection source, there are no reported cases of hematogenous P. micra pneumonia in healthy adults lacking a remote source of infection. Herein, we described the intact disease of P. micra-related pneumonia mimicking hematogenous Staphylococcus aureus pneumonia in terms of chest imagery and diagnosed via metagenomic next-generation sequencing (mNGS). Interestingly, there was no clear remote pathogenic source identified in the patient. Microbiome analysis revealed dysbiosis of the oral flora possibly related to poor oral hygiene and a long history of smoking. The patient was treated with moxifloxacin for 3 months. Ultimately, computed tomography (CT) of the chest showed total resolution of the lung lesion. Clinicians need to update the etiology of community-acquired pneumonia. When antibiotic therapy is not effective, pathogen examination becomes very important. New methods of pathogen detection such as mNGS should be employed to this end. For the treatment of P. micra pneumonia, no standardized course of treatment was reported. Imaging absorption of lung infections may provide a more objective guidance for the duration of antibiotics in P. micra pneumonia.